2019
DOI: 10.17977/um026v4i12019p014
|View full text |Cite
|
Sign up to set email alerts
|

The IMPLEMENTATION OF RECIPROCAL TEACHING MODEL TO IMPROVE STUDENTS’ ACHIEVEMENT ON ACID-BASE CONCEPTS

Abstract: This study aimed to describe the improvement of students' learning outcomes using reciprocal teaching model. The improvement is measured based on the results of pre-test and posttest. 24 students of XI class at SMA Negeri 4 Wangi-Wangi taking sciences major participated in this study. This one group pre-test & post-test research design used an instrument (test) in the form of multiple choice questions. The questions were constructed by considering the cognitive level in Bloom taxonomy. The study reveals that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Yunitasari et al, 2019). Therefore, teachers need to prepare a good understanding of the basic concepts of chemistry in high school as initial knowledge during further studies (Maysara & Habiddin, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Yunitasari et al, 2019). Therefore, teachers need to prepare a good understanding of the basic concepts of chemistry in high school as initial knowledge during further studies (Maysara & Habiddin, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Alemu [23] improved secondary physics teaching in content-and exam-oriented courses by combining interactive peer-her tutoring with a direct teaching approach. Researchers have found that reciprocal education is beneficial to English comprehension and can be used in science subjects to demonstrate very different scientific concepts [24]. Ahiri, Yuniarsih, and Rasto [21] examined how changes in peer learning and group study models affected students' critical thinking skills.…”
mentioning
confidence: 99%
“…Multi-tier instruments including two-tier, three-tier and four-tier levels have been developed and used to identify the understanding of concepts in several chemistry topics, including chemical kinetics (Habiddin & Page, 2019;Yan & Subramaniam, 2018), chemical equilibrium (Dewi et al, 2020), thermodynamics (Sreenivasulu & Subramaniam, 2013), transition metal chemistry (Sreenivasulu & Subramaniam, 2014), and the acid-base characteristic of salt solutions (Habiddin et al, 2020;Husniah et al, 2019) The source of misconceptions is not only caused by students' prior knowledge that is intuitive but also because of inappropriate learning strategies, commonly known as school-made misconceptions (Barke et al, 2008). The efforts to improve students' understanding of concepts and alleviate students' misconceptions have been carried out by using various learning strategies, including reciprocal teaching on acid-base material (Maysara & Habiddin, 2019), the text of the conceptual change and experiments on topics and their transformations and physical inorganic chemistry (Durmuş & Bayraktar, 2010;Rohmah et al, 2020) excel-based modelling (Malone et al, 2018), and concept-oriented learning change on gas topics (Cetin et al, 2009) The efforts to overcome misconceptions can be carried out on regular and remedial learning. Learning Cycle-6E is a learning model that refers to a constructivist approach that is believed to be able to create a precise learning environment to reduce and overcome students' misconceptions.…”
mentioning
confidence: 99%